(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study demonstrates the effect of casticin on esophageal squamous cell carcinoma cell lines, TE-1 and TE-15. The cells were treated with various concentrations (10-50 ?M) of casticin for different time periods. The results revealed that casticin treatment significantly inhibited the rate of cell proliferation in both TE-1 and TE-15 cell lines after 48 hours. Casticin treatment induced cell cycle arrest in S phase, enhanced the expression of proapoptotic gene, Bax and activation of caspase-3. Moreover, the morphological features of the cells were altered resulting in apoptosis. Casticin also inhibited the migration potential of TE-1 cells. Thus, casticin exhibits inhibitory effect on the esophageal squamous cell carcinoma cell lines by inhibiting cell proliferation, arresting cell cycle, inducing apoptosis and inhibiting migration. Therefore, casticin can be of therapeutic importance for the treatment of esophageal squamous cell carcinoma.